Evidence to support the classification of hyperglycemia first detected in pregnancy to predict diabetes 6–12 weeks postpartum: A single center cohort study. (November 2020) - Coetzee, Ankia; Sadhai, Nishendra; Mason, Deidre; Hall, David R; Conradie, Magda
Abstract: Aims: Diagnostic criteria for type 2 diabetes mellitus (T2DM) applied to women with gestational diabetes mellitus (GDM) may predict postpartum T2DM but requires validation. Methods: Women with GDM aged ≥ 18-years were prospectively evaluated 6–12 weeks after delivery at Tygerberg Hospital, Cape Town, South-Africa (November 2015- December 2018). Glucose status at GDM diagnosis was categorized into i) International Association for Diabetes in Pregnancy Study Group (IADPSG) T2DM (fasting glucose ≥ 7 mmol/L and/or 2hr-glucose ≥ 11.1 mmol/L) or ii) modified National Institute for Care Excellence (NICE) GDM (fasting glucose ≥ 5.6 mmol/L-6.9 mmol/L and/or 2hr-glucose ≥ 7.8 mmol/L-11 mmol/L) and compared with postpartum OGTT. Results: IADPSG T2DM and NICE GDM was present in 35% (n = 64) and 65% (n = 117) of the 181 women who completed the 8 ± 2 weeks postpartum evaluation respectively. Postpartum, the prevalence of T2DM and prediabetes was 26% (n = 47/181) and 15% (n = 28). Antenatal IADPSG T2DM categorization identified 31/47 women with postpartum T2DM (sensitivity 75%; specificity 48%). All of the modified NICE GDM category women who developed T2DM (n = 16/117) had elevations of both fasting and 2hr-glucose values antenatally. Conclusion: The utility of the IADPSG T2DM criteria to predict T2DM postpartum is confirmed. Women with both fasting and 2hr-glucose values above GDM cut-offs emerged as another high-risk category.